Capacidades estatais na pós-graduação: o olhar do secretário do Triângulo Mineiro e região - Oliveira, Juliana Bárbara da Silva (2022)
This research aimed to understand how State capacities in graduation offices (PPG) of the Triângulo Mineiro region are shaped. The approach was mostly qualitative. Regarding methodological procedures, individual interviews with secretaries of Graduation Offices of the Triângulo Mineiro region were conducted. This data source was complemented by documental research; afterwards, a non-structured observation with spontaneous findings was executed, followed by participation in a WhatsApp group. Lastly, individual surveys were conducted to set the triangulation process. The data analysis technique employed was traditional content analysis according to Bardin (2016). As a result, all capacities gathered by the literature at a micro level (Administrative, Regulative, Institutional, Fiscal, Political, Financial, Analytical, and Assessment) are exerted at the PPGs offices while the activities of the sectors are processed. Usually, secretaries exert their analytical capacity in using the accumulated experience from their secretary careers to help in process solution at the offices, and in doing so they contribute to the achievement of graduation programs’ goals. In contrast, secretaries informed that at the initial stages of their work at PPGs, they would not receive any training at all, nor documented processes or charts that could provide instructions to begin their activities. However, the secretaries’ WhatsApp group is currently an option for exchange of information and experience pertaining to everyday activities.